Hudhuri’s Epistemology in The Perspective of Mulla Shadra’s Philosophy of Knowledge - Efendi Efendi; Gazali Gazali; Endrika Widdia Putri; Salsa Hamidah Efendi (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This article aims to explore the thought of the Muslim philosopher Mulla Shadra (1572-1641 AD) regarding the philosophy of knowledge. The philosophical construction of this philosopher's knowledge is based on the teachings of al-Hikmah al-Muta'aliyyah which is the magnum opus of his philosophy. The main characteristic of the teachings of al-Hikmah al-Muta'aliyyah is the recognition of its characters about the source of knowledge, namely the combination of truth that comes from the revelation which is integrated with the ratio of vision and intuition or what is called hudhuri knowledge. This article is qualitative research using description and idealization methods. The results of this study are that Mulla Sadra's construction of hudhuri knowledge is different from the hudhuri knowledge put forward by Suhrawardi (1154-1191 AD)—a philosophy that also talks about hudhuri knowledge. Hudhuri Mulla Sadra's pattern of knowledge, namely; first, the distinctive feature of Mulla Sadra's hudhuri epistemology lies in the ability of hudhuri knowledge which is not only limited to personal experience/self-knowledge or cannot touch the realm of rationality, but can be applied to intellect and other knowledge. The method of acquiring hudhuri knowledge in Mulla Shadra's view is by making four journeys: the first journey leads the seeker to control his desires and leads to cleansing the heart. On the second and third trips, the salik will be able to feel ma'rifah and at the end of the third journey the salik is in the guardianship area, then the salik gets hudhuri knowledge